PENUMBUHKEMBANGAN PERILAKU BERTANGGUNGJAWAB ANAK USIA DINI PADA KELUARGA HINDU KOTA MATARAM - BUDHAWATI, NI PUTU SUDEWI (Program Studi Magister Pendidikan Anak Usia Dini, 2017)
Abstract:This research aims as follow to determine the processes, outcomes and constraints faced by Hindu family in growing responsible behavior in Mataram City. This research is almed to knowfaced by Hindu family in growing responsible behavior.This study was a qualitative research by using sociological approach. Data were collected by using observation, interview, and document study.Data analysis in this research was conducted during and after data collection by using qualitative data analysis of groove model developed by Miles and Huberman with reduction stage, data presentation and verification. Data analysis is presented in the form of reduction, classification, display and interpretation. The findings of the study were 1) the process of embodying responsible behavior of early childhood namely: (a) formal education, (b) non-formal education, and(c) informal education, 2) the result of embodying responsible behavior of early childhood is there were significant changes of children’s attitude. Their children become emphatic towards others, more friendly, more diligent, and more discipline. 3) The obstacles, of Hindu family appeared because of internal and external factor. It is advisable: every Hindu family should begin to develop good behavior toward their children from an early age. Key words: Growing, responsible behavior, early childhood. Abstrak: Penelitian ini bertujuan untuk mengetahui proses, hasil dan hambatan-hambatan yang dihadapi dalam penumbuhkembangan perilaku bertanggungjawab anak usia dini pada keluarga Hindu di Kota Mataram.Penelitian ini merupakan penelitian kualitatif dengan pendekatan sosiologis, penentuan informan dalam penelitian ini menggunakan teknik purposive dan teknikpengumpulan data yang dipergunakan adalah observasi, wawancara dan studi dokumentasi.Analisis data dalam penelitian ini dilakukan selama dan sesudah pengumpulan data dengan menggunakan analisis data kualitatif model alur yang dikembangkan oleh Miles dan Huberman dengan tahapan reduksi, penyajian data dan verifikasi. Analisis data disajikan dalambentuk reduksi, klasifikasi, display dan interpretasi.Hasil penelitian menunjukkan bahwa: 1) Proses menumbuhkembangkan perilaku bertanggungjawab anak usia dini melalui: (a) Pendidikan Formal, (b) Pendidikan Non Formal, dan (c) Pendidikan Informal. 2) Hasil penumbuhkembangan perilaku bertanggungjawab anak usia dini, diketahui bahwa terjadi perubahan yang sangatsignifikan terhadap perilaku anak. Anak menjadi lebih berempaty terhadap orang lain, lebih ramah, lebih rajin dan lebih disiplin, 3) Hambatan-hambatan yang dihadapi, yaitu karena muncul dari faktor internal anak dan dari faktor Eksternal. Kata Kunci: Penumbuhkembangan, bertanggungjawab, anak usia dini